ISOLATION AND CHARACTERIZATION OF RESISTANCE GENE ANALOGUE (RGA) FROM FUSARIUM RESISTANT BANANA CULTIVARS - Sutanto, Agus; Sukma, Dewi; Hermanto, Catur; Sudarsono, Mr. (Emirates Journal of Food and Agriculture, 2014)
Isolation and characterization of resistance genes from local banana cultivars was important in order to support the development of FOC resistant banana cultivars. Resistance gene analogues (RGAs) were isolated and characterized form three fusarium resistant banana cultivars using degenerate primers based on NBS domains. From 91 fragments sequenced, 17 fragments were positively NBS-type sequences and encoded as MNBS1-MNBS17. Phylogenetic analysis of MNBS deduced amino classified into three groups; the first group consisted of 14 members (MNBS1-MNBS14) with 97.4% identity, and the other three groups consisted of one member (MNBS15, MNBS16 and MNBS17, respectively) with 28.5% identity. All MNBS sequences were categorized as non-TIR-NBS-LRR. Comparison and phylogenetic analysis of MNBS with other known RGA and R genes showed that deduced amino acid MNBSs shared 91.7-98.8% identity with Musa NBS-LRR and 19.9-35.5% identity with known R genes. Among them, MNBS17 shared 50.5% identity with RGC2 (ABY75802) that assosiated to FOC race 4 resistant Musa species.